RETRACTED: Crop insurance as a risk management tool in agriculture: The case of silk farmers in northern Iran. (May 2017) - Farzaneh, Majid; Allahyari, Mohammad S.; Damalas, Christos A.; Seidavi, Alireza
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Editor. After a thorough investigation, the Editor has concluded that the acceptance of this article was based upon the positive advice of two illegitimate reviewer reports. The reports were submitted from email accounts which were provided by the corresponding author C.A. Damalas as suggested reviewers during the submission of the article. Although purportedly real reviewer accounts, the Editor has concluded that these were not of appropriate, independent reviewers. This manipulation of the peer-review process represents a clear violation of the fundamentals of peer review, our publishing policies, and publishing ethics standards. Apologies are offered to the reviewers whose identity was assumed and to the readers of the journal that this deception was not detected during the submission process.